Instructional Leadership of University Rectors as Professional Development for Employee Work Climate - Vitasari, Any Diana; Maisyaroh, Maisyaroh (Universitas Negeri Malang, 2024)
This study aims to examine the influence of instructional leadership on the work climate of employees at Bakti Indonesia University. Using a quantitative survey method, the research involved 95 respondents selected randomly. Data analysis using multiple linear regression showed that instructional leadership significantly affects the work climate, contributing 90.4%. These results align with previous studies that emphasize how supportive leadership styles, as described by Hallinger (2012) and Arici (2018), can enhance the quality of the work environment and productivity. Effective instructional leadership has been proven to create a harmonious work atmosphere, motivate employees, and support their well-being. These findings underline the importance of instructional leadership in shaping a positive work climate at universities.